1、 x = - a 3 x = a 1 n-1 2 3n-1 x = 5 14 = - 4m - 4 m + 3 2m -1 0 x + x = 4m n + 3 0 2 1 2 m -1 2m - 3 0 m m 3 0 m m 1 - 3 m 03 2 2 2 2 = - 4m - 4 1 4m - 4m -5 0 m - 5 4 - 5 4 m 1 m m x x - 2x + k = 0 x x y = x + x 2 1 2 1 3 2 3 y = x + x = x + x x + x - 3x x 1 3 2 3 1 2 1 2 2 1 2 1 1 1 2 2 2 1 1 2 x
2、x x x x x + + x +x x - x x + x |x - x | x x +x x 1 2 2 2 1 2 1 3 2 3 1 2 1 2 2 1 2 2 y -10 - y -10 1 2 93 93 x = y 2 = -8 - 93 x = y + 2 = -8 1 1 2 2 93 n = x x = - 8 - 93 -8 + 93 = 64 - 93 = -29 1 2 + + 1 1 + = - 10 3= + + + = + + + + + = + + + 8 3 1 1 1 1 1 2 2 ( ) + + + = + - + + = + - - = - + +
3、= + + - = - 1 1 2 8 3 8 3 10 3 2 148 30 1 1 1 8 3 1 10 3 1 10 2 2 ( ) ( ) + + 1 1 x x 2 148 30 1 10 0 + - = ( ) ( ) ( ) ( ) + - + + + + + 2 2 2 - 2 x + x = a x x = b +1 a = x + xb = x x -1 1 2 1 2 1 2 1 2 = x + x + 2x x + x x - 2x x +1 = x + x + x x +1 = x +1 x +1 1 2 2 2 1 2 1 2 2 2 1 2 1 2 2 2 1 2
4、 2 2 1 2 2 2 x x x +1 x +1 1 2 1 2 2 2 x + x + x x +1 x 1 x 1 1 2 2 2 1 2 2 2 1 2 2 2 10 11 3.162 3.317 x = -1+ 11 3 x = -1 - 11 3 1 2 x = 11 3 -1 -1 10.6 3317 3 . x x x 15 15 15 15 2 x 6 6 - + x x x x x x x x x x - + - + = - + - - + + 15 15 15 15 6 15 15 15 15 15 6 1 2 2 = x x 15 15 x x 15 - x + x 15 2 ( ) 15 15 15 6 2 - + x x x = -1+ 41 4 x = -1 - 41 4 1 2 2x + x -5 = 2 x - -1+ 41 4 x - -1 - 41 4 2